"Hurt people hurt people": Relations between adverse experiences and patterns of cyber and in‐person aggression and victimization among urban adolescents. Issue 4 (12th April 2021) - O'Connor, Kelly E.; Sullivan, Terri N.; Ross, Katherine M.; Marshall, Khiya J.
Abstract: This study identified subgroups of adolescents with distinct patterns of involvement with overt and relational in‐person and cyber aggression and victimization. We also assessed subgroup similarities and differences in exposure to adverse childhood experiences (ACEs), exposure to community violence, and trauma symptoms. Using latent class analysis, we identified three subgroups among 265 adolescents ( M age  = 14.3 years; 57% female; 96% African American) residing in three urban high‐burden communities that included youth who reported: (a) combined (cyber and in‐person) aggression and victimization (17%), (b) in‐person aggression and victimization (51%), and (c) adolescents with limited involvement (32%). Youth in the combined aggressive‐victims subgroup had the highest probability of endorsing exposure to community violence, trauma symptoms, and a higher number of ACEs overall as well as higher rates of both verbal and physical abuse compared to the other subgroups. Our results indicated that the adolescents who reported the highest frequencies of aggressive behavior were also the most victimized and traumatized. These findings provide context to aggressive behavior among adolescents living in high‐burden, urban communities and underscore the need for trauma‐informed prevention interventions.